THE IMPORTANCE OF INVENTORY MANAGEMENT IN A FOOD PRODUCTS INDUSTRY AND THE USE OF THE ERP SYSTEM - Garcia, Hugo Felipe; Reis Filho, Ramilio Ramalho (Revista Interface Tecnológica, 2022)
Managing a company’s inventory has always been a role of great importance. In times not too distant, organizations thought that keeping voluminous inventories was synonymous with wealth. Over the years, inventories stopped being accumulative and started to have only what was necessary for production, an essential factor for the economy. The food produced as well as its raw materials, due to the fact that they are perishable, cannot be stored for a long time, so specifically in the food industries, inventory management is extremely important as a way of saving and reducing waste, in addition to that fresher products end up generating production with more quality and efficiency. Within this context, the objective of this study is to bring the importance of inventory management and how it happens within a food industry. The work brings a literature review and field research in a food industry that sees the inventory management process as an essential factor for ensuring productivity and competitiveness. The company uses the ERP System as a tool for inventory management. The results found in the literature point to the efficiency of the inventory management process and how to manage this process brings important benefits.